Black shank-mediated alteration of the community assembly of rhizosphere soil bacteria in tobacco - Ma, Junchi; Chen, Jili; Zhang, Qing; Dong, Yumei; Li, Zhihua; Xie, Junqiu; Yang, Dongmei; Zhou, Lequn; Yan, Dahao; Zhou, Bo; Liu, Tao (Frontiers in Microbiology, 2024)
Introduction There is a close and complex interaction between the elements in the aboveground-underground ecosystem during the growth and development of plants. Specifically, when the aboveground part of plants is infected by pathogens, it induces the plant rhizosphere to synthesize specific root exudates. Consequently, a group of beneficial rhizosphere soil bacteria is recruited to help plants resist diseases. However, the changes in the rhizosphere soil bacterial community of plants under infection by oomycete pathogens remain unknown. Methods Three experimental treatments were set up in this experiment: soils inoculated with P. nicotianae, no-inoculation with P. nicotianae, and a control. The control treatment was composed of soils without transplanted tobacco plants, with the pathogen inoculated twice at an interval of eight days to ensure a successful P. nicotianae infection. P. nicotianae inoculation treatments were designed using the hyphal block inoculation method. In the non-inoculation treatment, tobacco plants were grown normally without pathogen inoculation. The tobacco plants were grown in a greenhouse. Results This study demonstrates that tobacco plants recruit microorganisms at the rhizosphere level as a defense mechanism against disease after infection by the oomycete pathogen Phytophthora nicotianae. Specific rhizosphere soil bacteria were screened in vitro to promote tobacco growth in a biofilm-forming manner, which induced the systemic resistance of the plants to P. nicotianae. The recruitment of rhizosphere soil bacteria to the inter-root zone of tobacco plants after infection by P. nicotianae can help subsequently cultivated tobacco plants in the same soil resist pathogen infestation. Discussion In conclusion, the present study confirms that infestation caused by oomycete pathogens alters the composition of the plant rhizosphere soil bacterial community and recruits a specific group of beneficial microorganisms that induce disease resistance and promote plant growth, thereby maximizing the protection of progeny grown in the same soil against the disease.